Ridogrel Inhibits Systemic and Renal Formation of Thromboxane A2 and Antagonizes Platelet Thromboxane A2/Prostaglandin Endoperoxide Receptors upon Chronic Administration to Man - Weber, C; Beetens, J R; Tegtmeier, F; Van Rooy, P; Vercammen, E; Wouters, L; De Clerck, F (Thrombosis and Haemostasis, 1992)
The effects of ridogrel, a dual thromboxane A2 (TXA2) synthase inhibitor and TXA2/prostaglandin (PG) endoperoxide receptor antagonist, on systemic and renal production of prostaglandins and on platelet TXA2/PG endoperoxide receptors was evaluated upon chronic administration (300 mg b. i. d. orally, for 8 and 29 days) to man. Such a medication with ridogrel inhibits the systemic as well as the renal production of TXA2 as measured by the urinary excretion of 2,3-dinor-TXB2 and TXB2 respectively without inducing significant changes in systemic or renal PGI2 production. Simultaneously with the latter effects, the production of TXB2 by spontaneously coagulated whole blood ex vivo is inhibited (>99%) while that of PGE2 and PGF2α is largely increased. Administration of ridogrel causes a three- to five-fold shift to the right of concentration-response curves for U46619 in eliciting platelet aggregation; no tachyphylaxis is observed after 29 days of treatment in this respect. Apart from a reduction of serum uric acid levels with a concomitant increase in urinary uric acid excretion during the first days of treatment, no clinically significant changes in hematological, biochemical, hemodynamic and coagulation parameters occur during the 8 days or 29 days study. The study demonstrates that ridogrel is a potent inhibitor of the systemic as well as renal TXA2 synthase and an antagonist of platelet TXA2/PG endoperoxide receptor in man, covering full activity during 24 h at steady-state plasma level conditions without tachyphylaxis during 29 days of medication. The compound is well tolerated, at least during 1 month of administration.